Założenia i pytania badawcze programu badań milenijnych - Marta Młynarska-Kaletynowa (Przegląd Archeologiczny, 2017)
Due to the approaching 1000th anniversary of the Polish State, at the end of 1948 the Department for Studies on the Origins of the Polish State as part of the General Directorate of Museums and Cultural Heritage was established at the Ministry of Culture and Art. Prof. Aleksander Gieysztor, a historian and medievalist from the University of Warsaw, became the president of the institution, while vice-presidents were K. Majewski, a classical archaeology professor, and archaeologist, associate professor Z. Rajewski. The office for the Studies on the Origins of the Polish State that consisted of a few employees was directed by Ph.D. R. Kiersnowski. The Department was involved in excavations of the most significant strongholds of the Piast State and it conducted interdisciplinary source studies in 1949-1953.